Do children want skinny friends? The role of 'weight' in children‟s friendship preferences and inter-group attitudes - Palmer, Sally; Rutland, Adam (Anales de Psicología / Annals of Psychology, 2011)
This study examined developmental attitudes towards underweight stimuli using two different measures. Children aged 5 - 11 firstly attributed positive and negative traits to images of underweight, averageweight and overweight stimuli. A second measure investigated picture preference of the same stimuli for 3 different contexts (Total N=151). The trait attribution task revealed that weight bias overrode gender bias amongst female participants of all ages; girls significantly preferred underweight images to average-weight and overweight images. In the picture preference task, preferences for the underweight stimuli were given by both male and female 5 to 7 year olds, when selecting which stimuli they would have as a 'friend' or to 'take home to play'.